Glycolic acid adjusted to pH 4 stimulates collagen production and epidermal renewal without affecting levels of proinflammatory TNF‐alpha in human skin explants. (24th July 2020) - Narda, Mridvika; Trullas, Carles; Brown, Anthony; Piquero‐Casals, Jaime; Granger, Corinne; Fabbrocini, Gabriella
Abstract: Background: Glycolic acid (GA) is an effective way of reversing the signs of age and photodamage. GA enhances desquamation of the stratum corneum and induces biological responses that can help restore skin's integrity. GA can, however, cause irritation, especially when its concentration is high, and its pH is low. Thus, most commercially available products for home use contain relatively low GA concentrations and are partially neutralized to a pH around 4. Aims: The aim of this study was to determine the biological effects and relative efficacy of cosmetic formulations containing GA at concentrations ranging from 8% to 25% at pH 4 in human ex vivo skin explants. Methods: Human skin explants were topically treated with gel formulations and oil‐in‐water creams containing 8%, 10%, 15%, or 25% GA, adjusted to pH 4, daily for 5 days. The degree of desquamation, their effect on cell proliferation, and their impact upon total collagen levels were determined 24 hours later. Levels of tumor necrosis factor‐alpha (TNF‐α) were measured after days 3 and 6. Results: All formulations effectively induced desquamation in a concentration‐dependent manner. Total collagen levels were increased at all concentrations, with greatest effects at higher GA concentrations. No effect on TNF‐α expression was observed. Conclusions: These data suggest that partially neutralized GA formulations retain skin rejuvenating properties without causing irritation and inflammation and that their use can be tailored to individual needs based on the concentration of GA in the formulation.